The Urban Working Class Representation of Perunggu Band’s Ini Abadi - Catur Surya Permana; Ferry Matias; Rosikin (Jomantara Indonesian Journal of Art and Culture, 2026)
This article analyzes the lyrics and musical composition of a song by the band Perunggu titled “ Ini Abadi ”. Perunggu is known as a viral band that promotes ideas about the urban working class. The lyrics express the grievances of the working class in facing economic realities and the political alienation of power. The context of urban labor is tied to the oppression of time and mental effort, creating a polemic around social and cultural status. This band is recognized as “the office workers’ band,” reflecting a lifestyle that is commonly faced by band members in Indonesia, who juggle two professions: being musicians and holding primary jobs. In the music industry context, the creation and determination of lyrics and musical composition can hold significance regarding the urban societal context. The aim of this research is to dissect the lyrics and musical composition created by the band Perunggu, which represents the urban working class. The approach employs descriptive methods to analyze the song, utilizing theories of popular music analysis and cultural studies. The results indicate that this work represents the identity and anxieties of the urban working class through reflective lyrics and a composition that evokes a collective context of experience, resistance, and solidarity among the urban working class in Indonesia.